Decision support in a fieldable laboratory management during an epidemic outbreak of disease. Issue 3 (5th December 2016) - Vybornova, Olga; Gala, Jean-Luc
Abstract : Purpose: The purpose of this paper is to analyze the decision-making process and provide a decision support framework for deployment of an on-site analytical capacity (a fieldable laboratory (FL)) to contain an expanding outbreak and protect public health. Design/methodology/approach: The FL mission cycle consists of five successive interlinked phases with a set of operational functions (OFs) performed during the mission. The list of phases, OFs and their contents were iteratively developed during and after FL missions and validated with operational partners. Findings: The well-defined structure of the FL domain appears as the best functional basis for tracking the decision-making process across the whole mission cycle. Description of all the FL elements and information flows addresses the major issue of interoperability of resources used by similar international capacities (inter-)acting as operational partners in global response to the crisis. Originality/value: The work presents the first attempt in this field to systematically describe and chronologically organize the decisions taken by a FL manager and staff during all phases of the FL mission cycle. Definition of OFs with all the related information flows allows for comparison of procedures, their better planning and refining, validation of protocols, mutual training and operational improvement between FLs from different geographical, organizational and cultural origins.